Uji efek Hipnotik Sedatif ekstrak etanol Daun Ubi Jalar (Ipomoea batatas) terhadap Mencit Jantan Galur Swiss - William Leslie (Program Studi Farmasi UNAJA, 2024)
This study aimed to evaluate the hypnotic and sedative effects of ethanol extract from sweet potato leaves (Ipomoea batatas) in male Swiss mice. The experiment was conducted at the Pharmacology Laboratory, Universitas Adiwangsa Jambi. Mice were divided into five groups: negative control (0.5% NaCMC), positive control (diazepam 1 mg/kg BW), and three treatment groups receiving ethanol extract of Ipomoea batatas leaves at doses of 200, 400, and 600 mg/kg BW. Hypnotic effect was evaluated using sodium pentobarbital-induced sleep (50 mg/kg BW, i.p), with onset of sleep and sleep duration as observed parameters. The results demonstrated that the extract at 400 and 600 mg/kg BW significantly reduced sleep onset time and prolonged sleep duration compared to the negative control (p<0.05). The highest dose showed effects comparable to diazepam. These findings indicate the potential of Ipomoea batatas ethanol leaf extract as a natural sedative agent, supporting its traditional use and opening opportunities for phytopharmaceutical development.